Database Solutions / A Step-by-Step Approach to Building Databases - Begg Carolyn; Connolly Thomas (Addison-Wesley, 2000)
Do you carry the world on your shoulders? Are you responsible for designing and creating the databases that keep your business running? Includes CD-ROM. Preface, Background, Database Analysis and Design Techniques, Logical Database Design, Physical Database Design, Second Worked Example, Appendices, Glossary, References, Index.